2021
DOI: 10.4018/978-1-7998-6618-3.ch025
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Transfer Among Academics in Higher Education Institutions

Abstract: In this fourth industrial revolution, knowledge transfer is essential among experienced academics for cross-fertilisation of ideas. Academics or colleagues in higher education institutions (HEIs) should harness and share their intuitive knowledge, skills, and experience for better service delivery. The rationale attributes to the decrease in skilled professionals in academia, technophobia, age, and language barriers. The issues of physical and mental ability, communication barrier, lack of trust, policies affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Reviewed literature and the data collected through documental analysis and close-ended questionnaires highlighted the importance of effective communication in course organisation and management. The literature identified that communication methods and means in advocating effective channels pave the strategy for effective communication within course delivery (Enakrire, 2021). The need for effective communication has been elevated since using VLE in HE and through ever-changing times such as the current pandemic context (Cao, 2021; Marachi and Quill, 2020).…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reviewed literature and the data collected through documental analysis and close-ended questionnaires highlighted the importance of effective communication in course organisation and management. The literature identified that communication methods and means in advocating effective channels pave the strategy for effective communication within course delivery (Enakrire, 2021). The need for effective communication has been elevated since using VLE in HE and through ever-changing times such as the current pandemic context (Cao, 2021; Marachi and Quill, 2020).…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%
“…It further signifies the use of research-active academics in course development in having relevant and contemporary knowledge and optimising the course organisation and management (Leal Filho et al , 2018). Lack of digitisation is a serious issue associated with the mismanagement of course information and ineffective course delivery (Albalooshi and Shatnawi, 2021; Enakrire, 2021). Therefore, digitised approaches to announce urgent updates on course delivery (D8) were positioned in Level I and considered fundamental in improving NSS Q17.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Techniques and skills were at issue ( Kane et al, 2004 ). Some studies rated teachers highly for their personality attributes, such as approachability, passion, and enthusiasm ( Enakrire, 2021 ). The importance of leadership skills and expertise increased for students as they progressed through higher levels of academia ( Yielder and Codling, 2004 ).…”
Section: Introductionmentioning
confidence: 99%